Mass Gathering Medical Care: Resource Document for the National Association of EMS Physicians Position Statement. (2nd October 2015) - Schwartz, Brian; Nafziger, Sarah; Milsten, Andrew; Luk, Jeffrey; Yancey, Arthur
Abstract: Mass gatherings are heterogeneous in terms of size, duration, type of event, crowd behavior, demographics of the participants and spectators, use of recreational substances, weather, and environment. The goals of health and medical services should be the provision of care for participants and spectators consistent with local standards of care, protection of continuing medical service to the populations surrounding the event venue, and preparation for surge to respond to extraordinary events. Pre–event planning among jurisdictional public health and EMS, acute care hospitals, and event EMS is essential, but should also include, at a minimum, event security services, public relations, facility maintenance, communications technicians, and the event planners and organizers. Previous documented experience with similar events has been shown to most accurately predict future needs. Future work in and guidance for mass gathering medical care should include the consistent use and further development of universally accepted consistent metrics, such as Patient Presentation Rate and Transfer to Hospital Rate. Only by standardizing data collection can evaluations be performed that link interventions with outcomes to enhance evidence-based EMS services at mass gatherings. Research is needed to evaluate the skills and interventions required by EMS providers to achieve desired outcomes. The event-dedicated EMS Medical Director is integral to acceptable quality medical care provided at mass gatherings; hence, he/she must be included in all aspects of mass gathering medical care planning, preparations, response, and recovery. Incorporation of jurisdictional EMS and community hospital medical leadership, and emergency practitioners into these processes will ensure that on-site care, transport, and transition to acute care at appropriate receiving facilities is consistent with, and fully integrated into the community's medical care system, while fulfilling the needs of event participants.Key words: mass gathering medicine; event medicine; event medical care planning; EMS medical director; prehospital